Peran Hukum Administrasi Negara dalam Penyelesaian Penyalahgunaan Wewenang yang Menimbulkan Kerugian Negara - Wardana, Rian Ismi; Frinaldi, Aldri; Roberia, Roberia (Polyscopia, 2024)
This study explores the role of administrative law in addressing cases of abuse of authority resulting in state losses. In the context of the background, abuse of authority by government officials can lead to significant financial losses for the state. The primary research question posed is how administrative law can be utilized to resolve such cases of abuse of authority, and what contribution it makes to preventing and combating these practices in the future. The research methodology involves document analysis, case studies, and relevant literature review. The reported findings in this article indicate that administrative law plays a crucial role in upholding justice and accountability in handling cases of abuse of authority, by providing a clear legal framework and effective law enforcement mechanisms. The conclusion drawn from this article emphasizes the importance of implementing robust administrative law to prevent and address abuses of authority, as well as the need for collaboration between law enforcement agencies and the government to ensure integrity and transparency in governance.